The Effects of Digital Technology on Opportunity Recognition - Thomas Kreuzer; Anna-Katharina Lindenthal; Anna Maria Oberländer; Maximilian Röglinger (Business & Information Systems Engineering, 2022)
Recognizing opportunities enabled by digital technology (DT) has become a competitive necessity in today's digital world. However, opportunity recognition is a major challenge given the influence of DT, which not only disperses agency across various actors, but also blurs boundaries between customers, companies, products, and industries. As a result, traditional entrepreneurship knowledge needs to be rethought and the effects of DT on opportunity recognition need to be better understood. Drawing from opportunity recognition theory – as one of the central theories in the entrepreneurship domain – this study builds on a structured literature review to identify and explain three direct as well as three transitive effects of DT on opportunity recognition. These effects have been validated with real-world cases as well as interviews with academics and practitioners. In sum, this study contributes to descriptive and explanatory knowledge on the evolution from traditional to digital entrepreneurship. As a theory for explaining, the findings extend opportunity recognition theory by illuminating how and why DT influences opportunity recognition. This supports research and practice in investigating and managing opportunities more effectively.
Keywords: 000; Opportunity recognition; Digital entrepreneurship; Digital technology; Digital technology effects; Digital innovation